2006
DOI: 10.2478/s11756-006-0140-7
|View full text |Cite
|
Sign up to set email alerts
|

The first study on the bacterial flora of the european spruce bark beetle, Dendroctonus micans (Coleoptera: Scolytidae)

Abstract: Abstract:The European spruce bark beetle, Dendroctonus micans Kugelann (Coleoptera, Scolytidae), is one of the most serious pests of oriental spruce (Picea orientalis L.) in Turkey. In this study, we investigated bacterial flora of D. micans collected from different populations of the forests of Eastern Black Sea Region of Turkey from 2002 to 2004. Seven different bacteria were isolated from healthy, diseased and dead specimens based on the color of colony and morphology. According to morphological, physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 31 publications
(52 reference statements)
2
9
3
Order By: Relevance
“…The culturable fraction of gut microbiota of Dendroctonus rhizophagus was integrated by seven bacterial species. Similar results have been reported in the Dendroctonus frontalis, Dendroctonus valens, and Dendroctonus micans gut, where 13, 14, and 7 culturable bacteria species were recognized, respectively [35,55,59]. The scarce gut bacterial community is a common feature in all bark beetles studied, probably due mainly to the antibacterial activity of some monoterpenes present in pine resin and/or limitation of nitrogen sources [2,53].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The culturable fraction of gut microbiota of Dendroctonus rhizophagus was integrated by seven bacterial species. Similar results have been reported in the Dendroctonus frontalis, Dendroctonus valens, and Dendroctonus micans gut, where 13, 14, and 7 culturable bacteria species were recognized, respectively [35,55,59]. The scarce gut bacterial community is a common feature in all bark beetles studied, probably due mainly to the antibacterial activity of some monoterpenes present in pine resin and/or limitation of nitrogen sources [2,53].…”
Section: Discussionsupporting
confidence: 86%
“…This bacterial diversity is slightly lower than that observed in other bark beetles [35,54,59]. The gut-associated bacterial community in pupae was lower in number and diversity than in larvae and adults (Table 2).…”
Section: Discussioncontrasting
confidence: 43%
“…have been previously isolated or detected in Dendroctonus spp. [10,24,25]. Known for the ability to produce a myriad of extracellular enzymes such as cellulases [26], Serratia spp.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, P. aeruginosa and P. fluorescens were frequently isolated from insects (Sezen & Demirbag 1999;Sezen et al 2004Sezen et al , 2005. In previous studies, it was reported that this bacterium could infect Euproctis chrysorrhoea (Steinhaus 1963), and Dendroctonus micans (Coleoptera: Scolytidae) (Yilmaz et al 2006). A number of Pseudomonas species are important insect pathogens, i.e., P. chlororaphis (Bucher 1981), P. fluorescens (Sezen & Demirbag 1999) and P. aeruginosa (Osborn et al 2002).…”
Section: Discussionmentioning
confidence: 99%